The Screening of Learning Readiness of Students with Disabilities at SLB Aisyiah Krian Sidoarjo using Electroencephalography (EEG): Screening Kesiapan Belajar siswa disabilitas SLB Aisyiah Krian Sidoarjo dengan Elektroensefalografi (EEG) - Tining; Haq, Muhammad Amirul; Wijaya, Sulton Dedi; Oktaviani, Marista; Fayyadh, Alwan; Firmansyah, Hafiz (LPPM UNINUS, 2024)
This community service aimed to analyze the relationship between brain waves and the readiness levels of students with disabilities in learning by utilizing EEG (Electroencephalography) signals. EEG signals were used to record brain electrical activity associated with various mental states, including learning readiness. The method involved collecting data from students with disabilities by measuring brain waves before and during the learning process. The results of this study revealed a significant correlation between specific types of brain waves, such as alpha and beta waves, and the students' readiness to absorb learning materials. These findings are expected to provide new insights for developing more effective teaching methods tailored to the mental conditions of students with disabilities and serve as a reference for optimizing inclusive education curricula based on technology